Resilience among nurses working in paediatric wards in Brunei Darussalam: A qualitative study - Ramli, Nur Raihan; Hj Mohd Noor, Hjh Siti Nor'ainah; Zolkefli, Yusrita (Belitung Nursing Journal, 2021)
Background: Resilience has become highly relevant for nurses working to avoid the negative impact of stress and maximise the positive benefits. Objective: This study aimed to explore and describe experiences of resilience among nurses when they first started working in paediatric wards. Methods: A qualitative, interpretive descriptive approach was used to guide the study. Purposive sampling was employed to recruit 8 participants, which proved sufficient to achieve theoretical saturation. Semi-structured individual interviews were conducted in 2020 and audio recorded. An inductive analytic approach was utilised. Results: Three overarching themes arose from the analysis: (1) The transition period (2) Gaining the trust of others (3) Having a positive mindset. Conclusion: This study found that nurses used multiple strategies of resilience in order to cope with workplace stress when they first began the transition period. However, as they become familiar with the workplace and gain the trust of others, this factor enables nurses to have a positive outlook toward job setbacks.